FeCoNiMnRu high-entropy alloy catalyst as well as preparation method and application thereof

By preparing FeCoNiMnRu high-entropy alloy catalyst, using electrospinning technology and two-stage calcination method, the problem of limited electron transfer of existing catalysts was solved, and efficient catalytic hydrolysis of ammonia borane was achieved, which significantly improved catalytic activity and material stability. , satisfying the catalytic properties of high entropy alloys.

CN119215930APending Publication Date: 2024-12-31GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411358162.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the catalytic hydrolysis of ammonia borane hydrogen production process, the electron transfer of single metal or bimetal alloy catalysts is limited, resulting in the catalytic activity that cannot meet the practical application requirements, and the catalytic characteristics of high-entropy alloys cannot be achieved through conventional alloys.

Method used

The FeCoNiMnRu high-entropy alloy catalyst was designed and prepared, and a variety of metals were uniformly dispersed in polymer fibers through electrospinning technology, and high-entropy alloy nanoparticles were formed through preoxidation and carbonization reduction processes, and the alloy structure was optimized by two-stage calcination method.

Benefits of technology

Achieve efficient catalytic ammonia borane hydrolysis hydrogen production, with a hydrogen evolution conversion frequency of 50-70molH2·molRu-1·min-1, a hydrolysis time of hydrogen release is 110-150s, a catalytic activation energy is 40-50kJ·mol-1, and a After 5 cycles, the initial activity is maintained at 40-50%, and it has excellent hydrogen production catalytic properties and material stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215930A_ABST
    Figure CN119215930A_ABST
Patent Text Reader

Abstract

The invention discloses a FeCoNiMnRu high-entropy alloy catalyst which is prepared by the following steps: preparing a high-entropy alloy spinning film from a Fe source, a Co source, a Ni source, a Mn source and a Ru source through an electrostatic spinning method, and then preparing the FeCoNiMnRu high-entropy alloy catalyst through a two-stage calcination method, the first-stage pre-oxidation calcination of the two-stage calcination method is used for realizing the pre-oxidation of the high-entropy alloy spinning membrane, and the second-stage carbonization reduction calcination is used for realizing the carbonization of the high-entropy alloy spinning membrane and the reduction of metal. The preparation method comprises the following steps: 1, preparing a FeCoNiMnRu high-entropy alloy electrostatic spinning membrane; and 2, the FeCoNiMnRu high-entropy alloy is prepared. When the catalyst is applied to catalysis in the aspect of hydrogen production through hydrolysis of ammonia borane, the hydrogen evolution conversion frequency is 50-70 mol H2. Mol Ru <-1 >. Min <-1 >, the hydrolysis hydrogen evolution time is 110-150 s, and the activation energy Ea is 40-50 kJ. Mol <-1 >; and after 5 cycles, 40-50% of initial catalytic activity is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic hydrogen production, and in particular to a FeCoNiMnRu high entropy alloy catalyst and a preparation method and application thereof. Background Art

[0002] The catalyst for hydrogen production by hydrolysis of ammonia borane is mainly composed of active metals and carriers. The active metals are mainly noble metal catalysts and non-noble metal catalysts; the carriers are mainly carbon materials or inorganic carriers with high specific surface area and high active sites.

[0003] Among them, precious metal catalysts such as the existing literature 1 (Yao, Q.; Shi, W.; Feng, G.; Lu, Z.-H.; Zhang, X.; Tao, D.; Kong, D.; Chen, X. Ultrafine Ru nanoparticles embedded in SiO2 nanospheres: Highly efficient catalysts for hydrolytic dehydrogenation of ammonia borane. J. Power Sources. 2014) were prepared to prepare ultrafine Ru nanoparticle catalysts embedded in SiO2 nanospheres, and the hydrogen evolution conversion frequency of catalyzing the hydrolysis of ammonia borane to produce hydrogen was obtained at room temperature. 49.1 mol H2 ·mol Ru -1 ·min -1 Although precious metals have excellent performance as catalysts in catalyzing the hydrolysis of ammonia borane to produce hydrogen, the disadvantage of high cost is an inherent attribute of such precious metal catalysts.

[0004] At the same time, non-precious metal catalysts such as the existing literature 2 (Zhou L, Jing M, Pan L, et al. Ultrasmall cobalt nanoparticles supported on nitrogen-doped porous carbon nanowires for hydrogen evolution from ammonia borane [J]. Materials Horizons, 2017) prepared nitrogen-doped porous carbon nanowires and cobalt nanoparticles Co / NPCNW catalysts, and obtained a hydrogen evolution conversion frequency of 7.29 mol / L for catalytic hydrolysis of ammonia borane to produce hydrogen under room temperature conditions. H2 ·mol Co -1 ·min -1Non-precious metal catalysts are loaded on the surface of a carrier and use the interaction between the catalyst and the carrier to adjust the electronic structure of the catalyst, thereby improving its catalytic activity. Although non-precious metal-based catalysts can achieve a significant improvement in catalytic performance, and some materials can achieve the catalytic performance of precious metal catalysts, they still cannot meet the requirements of practical applications.

[0005] According to existing documents 1 and 2, the use of a single metal as a catalytically active substance cannot meet the application requirements. Therefore, the current common technical solution is to use a multi-metal alloy obtained by compounding precious metals and non-precious metals as a catalyst. For example, existing document 3 (Rachiero, GP; Demirci, UB; Miele, P. BimetallicRuCo and RuCu catalysts supported onγ-Al2O3. A comparative study of their activity in hydrolysis of ammonia-borane. Int. J. Hydrogen Energy. 2011), by loading ruthenium copper bimetallic nanoparticles on γ-Al2O3, RuCo (1:1) / γ-Al2O3 catalyst was prepared, and the hydrogen evolution conversion frequency of catalyzing the hydrolysis of ammonia borane to produce hydrogen was obtained at room temperature. 32.9 mol H2 ·mol Ru -1 ·min -1 Although this technical solution achieves the synergistic effect between Ru and Cu bimetallics and improves the hydrolysis performance by combining non-precious metals and precious metals to form a bimetallic alloy, it still cannot meet the application requirements. The reason is that this technical solution only adjusts the metal composition of the alloy, and there is still the problem of limited electron transfer between the two metals, resulting in the number and activity of its catalytic activity still failing to meet the requirements.

[0006] High-entropy alloys are referred to as HEA. Their main feature is that they are alloys formed by five or more metals in equal or nearly equal amounts. According to the latest research, high-entropy alloys, as an emerging type of alloy, have a unique cocktail effect, especially in the field of catalysis, and have properties that conventional alloys do not have. However, the current conventional multi-metal alloys do not meet the characteristics of high-entropy alloys, that is, the main metal components in the previous alloys may be only one or two. The reason is that in the traditional field, the research results on alloy properties believe that introducing too many metal types into the alloy will cause the structural disorder of the alloy, thereby causing the alloy performance to deteriorate. However, the structural characteristics of high-entropy alloys are different from those of conventional alloys. High-entropy alloys avoid the structural disorder of conventional alloys caused by too many metal types through the characteristics of homogeneous structure, and obtain unique properties. In other words, the current conventional alloy-type catalysts, because they are conventional alloys, do not have the catalytic characteristics of high-entropy alloys and cannot achieve the catalytic effect of high-entropy alloys. Summary of the invention

[0007] The purpose of the present invention is to provide a FeCoNiMnRu high entropy alloy catalyst and its preparation method and application. The basic principles of the present invention mainly include the following two aspects:

[0008] 1. According to the differences in electronegativity and atomic radius between elements, non-precious transition metal elements Fe, Co, Ni, Mn and precious metal element Ru with small differences in electronegativity and atomic radius were selected to design and synthesize FeCoNiMnRu high entropy alloy;

[0009] 2. Through electrospinning technology, multiple metals are evenly dispersed in polymer fibers, and through subsequent pre-oxidation and carbonization processes, multiple metals are reduced together to form high-entropy alloy nanoparticles.

[0010] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0011] A FeCoNiMnRu high entropy alloy catalyst is prepared from Fe source, Co source, Ni source, Mn source and Ru source, firstly through an electrostatic spinning method to prepare a high entropy alloy spinning membrane, and then through a two-stage calcination method to prepare the FeCoNiMnRu high entropy alloy;

[0012] The Fe source is anhydrous ferric chloride, the Co source is cobalt chloride hydrate, the Ni source is nickel chloride hydrate, the Mn source is manganese chloride hydrate, and the Ru source is ruthenium chloride hydrate;

[0013] The raw materials of the high entropy alloy spinning membrane include Fe source, Co source, Ni source, Mn source and Ru source, and also include N,N-dimethylformamide and polyacrylonitrile;

[0014] The two-stage calcination method is divided into a first stage of pre-oxidation calcination and a second stage of carbonization reduction calcination, wherein:

[0015] The purpose of the first stage of pre-oxidation calcination is to achieve pre-oxidation of the high entropy alloy spinning membrane;

[0016] The purpose of the second stage of carburization reduction calcination is to achieve the carbonization of the high entropy alloy spinning membrane and the reduction of the metal.

[0017] A method for preparing a FeCoNiMnRu high entropy alloy comprises the following steps:

[0018] Step 1, preparation of FeCoNiMnRu high entropy alloy electrospinning membrane, first, manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate and ruthenium chloride trihydrate are mixed with N, N-dimethylformamide in a certain amount ratio of manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate, ruthenium chloride trihydrate, polyacrylonitrile and N, N-dimethylformamide, and ultrasonicated under certain conditions, and then magnetically stirred under certain conditions to obtain FeCoNiMnRu high entropy alloy spinning solution, referred to as electrospinning solution, and finally, electrospinning the electrospinning solution under certain conditions to obtain FeCoNiMnRu high entropy alloy electrospinning membrane, referred to as high entropy alloy spinning membrane;

[0019] In the step 1, the molar ratio of manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate and ruthenium chloride trihydrate is 1:1:1:1:1;

[0020] In the step 1, the ultrasonic condition is that the ultrasonic time is 30-60 min; the stirring condition is that the stirring time is 8-10 h;

[0021] In the step 1, the electrospinning conditions are: negative voltage is -3--2 kV, positive voltage is 10-15 kV, injection speed is 0.04-0.06 cm / min, and roller speed is 20-40 r / min;

[0022] Step 2, preparation of FeCoNiMnRu high entropy alloy, first, under certain conditions, the high entropy alloy spinning membrane obtained in step 1 is subjected to a first stage of pre-oxidation calcination, then, under certain conditions, a second stage of carburization reduction calcination is performed, and finally, the obtained product is ground to obtain FeCoNiMnRu high entropy alloy, referred to as FCNMR;

[0023] In the step 2, the conditions for the first stage of pre-oxidation calcination are: under air conditions, a heating rate of 3-5°C / min, a calcination temperature of 230-300°C, and a calcination time of 3-5h; in the step 2, the conditions for the second stage of carbonization reduction calcination are: under argon gas conditions, a heating rate of 3-5°C / min, a calcination temperature of 800-1000°C, and a calcination time of 3-5h.

[0024] A FeCoNiMnRu high entropy alloy catalyst, when used as a catalyst for hydrogen production by hydrolysis of ammonia borane, has a hydrogen evolution conversion frequency of 50-70 mol H2 ·mol Ru -1 ·min -1 The hydrolysis time is 110-150s, and the activation energy of catalytic hydrogen release is E a =40-50 kJ·mol -1 ;

[0025] At 25 °C, after 5 cycles, 40-50% of the initial catalytic activity was retained.

[0026] The beneficial technical effects of the material obtained by the present invention can be seen from the following tests:

[0027] XRD detection shows that the FeCoNiMnRu high entropy alloy catalyst has the characteristic peaks of a typical face-centered cubic structure, and no characteristic peaks of other crystal structures are detected;

[0028] SEM examination shows that the FeCoNiMnRu high entropy alloy catalyst presents an alloy nanoparticle structure, and the alloy nanoparticles are randomly embedded in the spherical carbon surface;

[0029] EDS tests show that there are five elements, Fe, Co, Ni, Mn and Ru, in the FeCoNiMnRu high entropy alloy catalyst, and they are evenly distributed in the alloy nanoparticles embedded in the spherical carbon surface;

[0030] The hydrogen production test shows that at 25°C, the hydrolysis time is 110-150s, and the hydrogen evolution conversion frequency is 50-70mol H2 ·mol Ru -1 ·min -1 ;

[0031] The reaction kinetics performance test shows that the apparent activation energy E of the reaction a =40-50 kJ·mol -1 ;

[0032] The cyclic performance test showed that after 5 cycles at 25°C, 40-50% of the initial catalytic activity was still retained.

[0033] Therefore, the present invention has the following advantages over the prior art:

[0034] 1. By selecting non-precious transition metal elements Fe, Co, Ni, Mn and precious metal element Ru, high entropy alloys that cannot be obtained by conventional multi-element alloys are realized;

[0035] 2. Through step-by-step calcination, i.e., pre-oxidation first, then carbonization reduction, multiple metals can be reduced simultaneously to obtain high entropy alloys. In addition, the electrostatic method technology can effectively improve the dispersibility of alloy nanoparticles;

[0036] 3. The raw materials used in the present invention are all commercially available, low cost, simple process, short reaction cycle, low energy consumption and low pollution;

[0037] Therefore, compared with the prior art, the present invention has better hydrogen production catalytic performance and material stability, and has broad application prospects in the field of hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a SEM image of the electrospun membrane prepared in step 2 of Example 1;

[0039] Figure 2 is the XRD pattern of FCNMR of Example 1;

[0040] Figure 3 It is the EDS test chart of FCNMR of Example 1;

[0041] Figure 4 It is the SEM picture of FCNMR of Example 1;

[0042] Figure 5 This is a FCNMR test diagram of the catalytic ammonia borane hydrolysis performance at different temperatures of Example 1;

[0043] Figure 6 This is the FCNMR catalytic ammonia borane hydrolysis performance test diagram of Example 1;

[0044] Figure 7 This is a test chart of the catalytic hydrolysis performance of ammonia borane by the CoNiMnRu medium-entropy alloy catalyst prepared in Comparative Example 1.

[0045] Figure 8 This is a test chart of the catalytic hydrolysis performance of ammonia borane of the FeCoNiMnRu high entropy alloy catalyst prepared by chemical reduction in Comparative Example 2. DETAILED DESCRIPTION

[0046] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0047] Example 1

[0048] A method for preparing a FeCoNiMnRu high entropy alloy comprises the following steps:

[0049] Step 1, preparation of FeCoNiMnRu high entropy alloy electrospinning membrane, first, with the molar ratio of manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate and ruthenium chloride trihydrate being 1:1:1:1:1, 0.0989g manganese chloride tetrahydrate, 0.0811g anhydrous ferric chloride, 0.1189g cobalt chloride hexahydrate, 0.1188g nickel chloride hexahydrate, 0.1037g ruthenium chloride trihydrate, 1.5g polyacrylonitrile and 23mL N,N-dimethylformamide The mixture was mixed and ultrasonicated for 30 min, and then magnetically stirred for 8 h to obtain a FeCoNiMnRu high entropy alloy spinning solution, referred to as an electrospinning solution. Finally, the electrospinning solution was electrospun under the electrospinning conditions of negative voltage of -3 kv, positive voltage of 15 kv, injection speed of 0.04 cm / min, and roller speed of 20 r / min to obtain a FeCoNiMnRu high entropy alloy electrospinning membrane, referred to as a high entropy alloy spinning membrane.

[0050] In order to verify the microstructure of the high entropy alloy spinning membrane obtained in step 1, SEM test was performed. The test results are shown in Figure 1 As shown, the high entropy alloy spinning membrane is composed of nanofibers.

[0051] Step 2, preparation of FeCoNiMnRu high entropy alloy, first, under air conditions, at a heating rate of 3°C / min, a calcination temperature of 230°C, and a calcination time of 3h, the high entropy alloy spinning membrane obtained in step 1 is subjected to a first stage of pre-oxidation calcination, then, under argon gas conditions, at a heating rate of 3°C / min, a calcination temperature of 800°C, and a calcination time of 3h, a second stage of carburization reduction calcination is carried out, finally, the obtained product is ground to obtain FeCoNiMnRu high entropy alloy, referred to as FCNMR.

[0052] Among them, the function of the first stage of pre-oxidation calcination is to achieve pre-oxidation of the high entropy alloy spinning membrane;

[0053] The purpose of the second stage of carburization reduction calcination is to achieve the carbonization of the high entropy alloy spinning membrane and the reduction of the metal.

[0054] In order to prove the crystal structure of FCNMR, XRD test was performed. The test results are as follows Figure 2As shown, the characteristic peaks of FCNMR are consistent with those of FeNi alloy, that is, the test results show that FCNMR has the same crystal plane structure as FeNi alloy.

[0055] In order to prove the composition of FCNMR, EDS test was performed. The test results are as follows Figure 3 As shown, FCNMR contains Fe, Co, Ni, Mn, Ru, and C elements at the same time, and the elements are evenly distributed.

[0056] In order to further prove that FCNMR is a high entropy alloy, ICP test was performed. The test results are shown in Table 1. The contents of the five elements are basically the same, which meets the content requirements of high entropy alloys.

[0057] Table 1 Element composition content table of FCNMR

[0058] Element Type Fe Co Ni Mn Ru Element content (wt.%) 5.05 6.14 6.25 2.59 4.07

[0059] In order to verify the microscopic morphology of FCNMR, SEM test was performed. The test results are shown in Figure 4 As shown, FCNMR shows that the nano alloy particles are loaded on spherical carbon, and the particle size of the alloy particles is 10-30nm.

[0060] In order to prove the performance of FCNMR as a catalyst for hydrogen production by hydrolysis of ammonia borane, a hydrolysis performance test was conducted. The specific test method of the hydrolysis performance test is: under standard atmospheric pressure and 25°C, 100 mg of the sample to be tested is placed in a wide-mouth bottle, 20 mL of deionized water is added and fully stirred and dispersed, and then the wide-mouth bottle is connected to a metering tube filled with water in a constant temperature water bath, and under magnetic stirring conditions, 10 mL of a 0.1 mmol / mL ammonia borane aqueous solution is injected, and finally, the volume of generated hydrogen is calculated by the water displacement method; among them, the hydrogen evolution conversion frequency is calculated by the hydrogen release time, which can reflect the reaction rate of hydrolysis and hydrogen release.

[0061] The hydrolysis performance test results of FCNMR are as follows Figure 5 As shown, the hydrolysis hydrogenation time is 150s, and the hydrogen evolution conversion frequency is 55.3molH2·molRu -1 ·min -1 , the hydrolysis rate is 100%.

[0062] In order to prove the kinetic performance of FCNMR as a catalyst for hydrogen production by hydrolysis of ammonia borane, hydrolysis performance tests were carried out at different temperatures, namely 20℃, 25℃, 30℃, and 35℃. Figure 5 As shown in Table 2, the activation energy of FCNMR was calculated by fitting the Arrhenius equation and Ea = 42.3 kJ·mol -1 .

[0063] Table 2 Hydrogen evolution conversion frequency and time required to complete hydrolysis and hydrogen evolution corresponding to catalytic hydrolysis of ammonia borane at different temperatures

[0064] Temperature(℃) 20 25 30 35 Time required to complete hydration and hydrogenation (s) 150 135 100 94 <![CDATA[Hydrogen evolution conversion frequency (mol H2 ·mol Ru -1 ·min -1 )]]> 43.34 55.31 78.15 104.17

[0065] In order to prove the cyclic performance of FCNMR, a cyclic performance test was conducted. The specific test method is: repeatedly injecting ammonia borane aqueous solution to perform hydrolysis performance test, and the cyclic performance test can be achieved. The test results are as follows Figure 6 As shown, after 5 cycles, the hydrogen evolution transition frequency of FCNMR is 16.78 mol H2 ·mol Ru -1 ·min -1 , the hydrolysis rate is 100%.

[0066] In order to demonstrate the effect of the preparation method, namely, the electrospinning method, on the properties of the prepared high entropy alloy, Comparative Example 1 is provided, in which the FeCoNiMnRu alloy is prepared by a chemical reduction method.

[0067] Comparative Example 1

[0068] A method for preparing a FeCoNiMnRu alloy, using the same raw materials and their proportions as in Example 1, namely 0.0989g of manganese chloride tetrahydrate, 0.0811g of anhydrous ferric chloride, 0.1189g of cobalt chloride hexahydrate, 0.1188g of nickel chloride hexahydrate, and 0.1037g of ruthenium chloride trihydrate as raw materials, and adopting a chemical reduction method to prepare the FeCoNiMnRu alloy. The specific steps of the chemical reduction method are as follows: first, placing the raw materials in 50mL of deionized water to obtain a reaction solution, and then, heating at room temperature. Under temperature conditions, 10 mL of saturated sodium borohydride solution was added to the reaction solution, and the mixture was vigorously stirred for 3 h to obtain a black precipitate. Finally, the black precipitate was washed and centrifuged under the conditions of ultrapure water and ethanol as washing liquid, a centrifugal speed of 8000 rpm, a centrifugal time of 5 min, and 5 washing times. Then, the black precipitate was dried at a drying temperature of 60 ° C and a drying time of 15 h to obtain FeCoNiMnRu alloy, referred to as FeCoNiMnRu-H.

[0069] The hydrolysis performance test results of FeCoNiMnRu-H are as follows Figure 7 As shown, the hydrolysis hydrogenation time of FeCoNiMnRu-H is 900s, and the hydrogen evolution conversion frequency is 1.74molH2·molRu -1 ·min -1The hydrolysis rate is 45%. The test results are compared with those of Example 1, and it can be seen that the FCNMR prepared by the electrostatic spinning method can significantly reduce the hydrogen release time and increase the hydrogen evolution conversion frequency, and the effect is obvious, which proves that the technical effect of the electrostatic spinning method is significantly better than the conventional chemical reduction method.

[0070] In order to demonstrate the formation of high entropy alloys, that is, the effect of transition metal element Fe on performance, comparative example 1 is provided, which is a medium entropy alloy without Fe.

[0071] Comparative Example 2

[0072] A method for preparing a CoNiMnRu medium-entropy alloy that does not contain Fe, wherein the steps not specifically described are the same as those in Example 1, except that when performing step 1, anhydrous ferric chloride is not added, that is, the necessary technical feature transition metal element Fe is reduced, and the obtained material is named CoNiMnRu medium-entropy alloy, abbreviated as medium-entropy alloy.

[0073] The performance test results of medium entropy alloy as a catalyst for hydrogen production by hydrolysis of ammonia borane are as follows: Figure 8 As shown, the hydrolysis hydrogen release time of the medium entropy alloy is 240s, and the hydrogen evolution conversion frequency is 36.1molH2·molRu -1 ·min -1 The hydrolysis rate is 100%. The test results show that the medium entropy alloy does not have a good catalytic effect on ammonia borane.

[0074] Compared with Example 1, it can be seen that the introduction of Fe element can transform the medium-entropy alloy into a high-entropy alloy, thereby significantly reducing the hydrogen release time and increasing the hydrogen evolution conversion frequency, that is, significantly improving the catalytic performance.

Claims

1. A FeCoNiMnRu high entropy alloy catalyst, characterized in that: A high entropy alloy spinning membrane is firstly prepared from Fe source, Co source, Ni source, Mn source and Ru source by electrostatic spinning method, and then FeCoNiMnRu high entropy alloy is prepared by two-stage calcination method.

2. The FeCoNiMnRu high entropy alloy catalyst according to claim 1, characterized in that: The Fe source is anhydrous ferric chloride, the Co source is cobalt chloride hydrate, the Ni source is nickel chloride hydrate, the Mn source is manganese chloride hydrate, and the Ru source is ruthenium chloride hydrate.

3. The FeCoNiMnRu high entropy alloy catalyst according to claim 1, characterized in that: The raw materials of the high entropy alloy spinning membrane include Fe source, Co source, Ni source, Mn source and Ru source, as well as N,N-dimethylformamide and polyacrylonitrile.

4. The FeCoNiMnRu high entropy alloy catalyst according to claim 1, characterized in that: The two-stage calcination method is divided into a first stage of pre-oxidation calcination and a second stage of carbonization reduction calcination, wherein: The purpose of the first stage of pre-oxidation calcination is to achieve pre-oxidation of the high entropy alloy spinning membrane; The purpose of the second stage of carburization reduction calcination is to achieve the carbonization of the high entropy alloy spinning membrane and the reduction of the metal.

5. A method for preparing a FeCoNiMnRu high entropy alloy, characterized in that The following steps are involved: Step 1, preparation of FeCoNiMnRu high entropy alloy electrospinning membrane, first, manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate and ruthenium chloride trihydrate are mixed with N, N-dimethylformamide in a certain amount ratio of manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate, ruthenium chloride trihydrate, polyacrylonitrile and N, N-dimethylformamide, and ultrasonicated under certain conditions, and then magnetically stirred under certain conditions to obtain FeCoNiMnRu high entropy alloy spinning solution, referred to as electrospinning solution, and finally, electrospinning the electrospinning solution under certain conditions to obtain FeCoNiMnRu high entropy alloy electrospinning membrane, referred to as high entropy alloy spinning membrane; In the step 1, the ultrasonic condition is that the ultrasonic time is 30-60 min; the stirring condition is that the stirring time is 8-10 h; Step 2, preparation of FeCoNiMnRu high entropy alloy, first, under certain conditions, the high entropy alloy spinning membrane obtained in step 1 is subjected to a first stage of pre-oxidation calcination, then, under certain conditions, a second stage of carburization reduction calcination is carried out, and finally, the obtained product is ground to obtain FeCoNiMnRu high entropy alloy, referred to as FCNMR.

6. The preparation method according to claim 5, characterized in that: In the step 1, the molar ratio of manganese chloride tetrahydrate, anhydrous ferric chloride, cobalt chloride hexahydrate, nickel chloride hexahydrate and ruthenium chloride trihydrate is 1:1:1:1:

1.

7. The preparation method according to claim 5, characterized in that: In the step 1, the electrospinning conditions are: negative voltage of -3-2 kV, positive voltage of 10-15 kV, injection speed of 0.04-0.06 cm / min, and roller speed of 20-40 r / min.

8. The preparation method according to claim 5, characterized in that: In step 2, the conditions for the first stage of pre-oxidation calcination are: in air, with a heating rate of 3-5°C / min, a calcination temperature of 230-300°C, and a calcination time of 3-5h; In step 2, the conditions for the second stage of carbonization reduction calcination are: under argon gas conditions, a heating rate of 3-5°C / min, a calcination temperature of 800-1000°C, and a calcination time of 3-5h.

9. A FeCoNiMnRu high entropy alloy catalyst, characterized in that: When used as a catalyst for hydrogen production by hydrolysis of ammonia borane, the hydrogen evolution conversion frequency is 50-70 mol H2 ·mol Ru -1 ·min -1 The hydrolysis time is 110-150s, and the activation energy of catalytic hydrogen release is E a =40-50 kJ·mol -1 .

10. A FeCoNiMnRu high entropy alloy catalyst, characterized in that: When used as a catalyst for hydrogen production by hydrolysis of ammonia borane, the catalyst maintains 40-50% of its initial catalytic activity after 5 cycles at 25°C.

Citation Information

Cited By

  • One-dimensional high-entropy alloy, preparation method and application of one-dimensional high-entropy alloy in CO2 cycloaddition reaction

    CN121447047A